2021
DOI: 10.1111/puar.13361
|View full text |Cite
|
Sign up to set email alerts
|

How Bureaucratic Representation Affects Public Organizational Performance: AMeta‐Analysis

Abstract: The impact of representative bureaucracy on public organizational performance has received a good deal of attention in public management. However, the literature provides little systematic rationalization about the effects of the individual constructs of representative bureaucracy on organizational performance. This meta-analysis of 648 effect sizes from 80 quantitative studies, closely examines the conditions under which bureaucratic representation affects public organizational performance. The research provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 150 publications
1
38
0
Order By: Relevance
“…The findings regarding the benefits of shared sociodemographic identities confirm the general takeaways from the representative bureaucracy literature (prior finding of Ding, Lu, and Riccucci 2021), which suggests that shared demographics between bureaucrats and civilians can reap benefits of increased coproduction (Hong 2016; Riccucci and Van Ryzin 2017). Specifically, police officers emphasized the practical utility of shared personal identity for the purposes of fostering comfort, preference, and information sharing from the community.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The findings regarding the benefits of shared sociodemographic identities confirm the general takeaways from the representative bureaucracy literature (prior finding of Ding, Lu, and Riccucci 2021), which suggests that shared demographics between bureaucrats and civilians can reap benefits of increased coproduction (Hong 2016; Riccucci and Van Ryzin 2017). Specifically, police officers emphasized the practical utility of shared personal identity for the purposes of fostering comfort, preference, and information sharing from the community.…”
Section: Discussionsupporting
confidence: 76%
“…The empirical research examining representative bureaucracy has been applied in a variety of policy and occupational contexts, and across these contexts, the theory of representative bureaucracy has often been used to examine demographic characteristics such as race and gender (Ding, Lu, and Riccucci 2021). Taken as a whole, this research has indicated that racial representation is associated with positive benefits such as reductions in police misconduct and overall crime rates (Hong 2016, 2017), increases in student pass rates on assessments (Pitts 2005), educational improvements for students of color (Grissom, Nicholson‐Crotty and Nicholson‐Crotty 2009), more federal contracts awarded to minority‐owned business (Fernandez, Malatesta, and Smith 2013), and improved perceptions and assessments of police performance by Black individuals (Riccucci, Van Ryzin, and Jackson 2018); and gender representation scholars have found benefits for girls in math classes (Keiser et al 2002), increased reports of sexual assaults and subsequent case resolutions for victims (Meier and Nicholson‐Crotty 2006), and greater willingness by women to coproduce in recycling programs (Riccucci, Van Ryzin, and Li 2016).…”
Section: Representative Bureaucracy Organizational Socialization and ...mentioning
confidence: 99%
“…The study speaks to a contextualized understanding of representative bureaucracy (Ding, Lu, and Riccucci 2021;Groeneveld et al 2015;Kennedy 2014;Meier 2019;Park 2021;Peters, Schröter, and von Maravić 2015). Expanding the study context is crucial for the scholarship to improve the explanatory power, solidify a shared consensus, and advance the theoretical and practical implications.…”
Section: A B C Dmentioning
confidence: 99%
“…The presence of women and minorities at higher level or supervisory positions increases active representation (Meier and Nigro 1976; Mosher 1968; Kanter 1977), while active representation frequently occurs at the street‐level (Meier and Stewart Jr 1992; Meier 1993; Thompson 1976). A recent meta‐analysis indicated that street‐level bureaucrats with expertise and discretion have a greater impact on citizens/clients and bureaucratic performance (Ding, Lu, and Riccucci 2021). However, only a few studies have examined both the supervisory‐level and street‐level representation within a bureaucratic organization (e.g., Agyapong 2018; Keiser et al 2002; Meier and Stewart Jr 1992; Wilkins and Keiser 2006, among others), and demographic congruence between supervisors (managers) and subordinates (frontline bureaucrats) (e.g., Grissom and Keiser 2011; Grissom, Nicholson‐Crotty, and Keiser 2012; Groeneveld and Meier 2021).…”
Section: Theory and Literaturementioning
confidence: 99%
“…Let us turn our focus to what the authors in this issue have to say about two important themes: Representativeness and pandemic crisis response. Beginning with articles oriented around representation, equity, and social justice, the lead article in this issue is a metaanalysis that explores bureaucratic representation and its effect on organizational performance (Ding, Lu, and Riccucci 2021). Their study reveals that the effects of representative bureaucracy on public organizational performance are positive, yet moderated by several contextual factors.…”
Section: When It Comes To Evidence You Get What You Pay For; So Do Not Go Cheapmentioning
confidence: 99%